Sustainable Development Strategies for Enhancing Gender Welfare in Kelurahan Kalitirti, Sleman Regency, Yogyakarta - Ashri Ramadhan (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2024)
This study explores sustainable development strategies to enhance gender welfare in Kelurahan Kalitirti, Sleman, Yogyakarta, with a primary focus on women's empowerment through integrated social and economic programs. Employing a qualitative research method, data were collected via in-depth interviews and participatory observation. The findings reveal that these programs significantly increased women's participation in local economic activities. Through various initiatives, women in this community have substantially contributed to the local economy and improved their families' welfare. Furthermore, the social support and skills training provided have bolstered women's independence and opened new business opportunities. The study concludes that this community-based sustainable development approach serves as an effective, replicable model for enhancing gender welfare in other regions. This approach not only positively impacts the economy but also addresses social aspects, reducing gender disparities at the local level.